The Future of Indonesian Asset Confiscation Through the Unexplained Wealth Order (UWO) Mechanism: A Comparative Study with the UK - Adinda Maura Salwa (Jurist-Diction, 2026)
This study conducts a normative legal analysis using a comparative approach to examine the asset confiscation laws in Indonesia and the UK. The main objective of the study is to evaluate the effectiveness and efficiency of the asset recovery mechanisms aimed at addressing state losses due to corruption. In the UK, the implementation of the Unexplained Wealth Order (UWO) has successfully navigated various legal and institutional challenges in the asset recovery process. In contrast, Indonesia continues to face obstacles due to its reliance on a conventional approach that necessitates criminal penalties before asset confiscation can occur. This study utilizes primary legal materials, such as regulations and jurisprudence, along with secondary legal resources, to identify the differences in procedures and institutions involved in asset confiscation between the two countries. The novelty of this lies in the description of the two-asset confiscation legal systems that, in previous studies often examined separately. The study results recommend that Indonesia should promptly ratify the Asset Confiscation Bill by adopting strategic elements from the UWO mechanism in the UK to enhance its asset recovery efforts.